Situer la possession. Du droit romain de l’appartenance aux nouveaux modèles propriétaires - Pierre Thévenin (Clio@Themis)
This article calls for a reengagement with historical forms of legal appropriation. Exploring ways to benefit from a ressource that ran parallel to exclusive property, it aims at providing legal scholars with an archeological touchstone capable of triggering new approaches to property rights. The Roman law of possession, it argues, offers a valuable angle for such an inquiry. Focusing on its interpretation by Savigny, it looks at the part it played in binding classical legal theory with the modern idea of personality.